Cognizance of Forensic Odontology among the Dental Practitioners in Lahore (Medical Forum Monthly, 2024)
Objective: To assess the knowledge towards forensic odontology among dental professionals and to evaluate the need for initiation of formal training in this subject.Study Design: Descriptive / cross sectional study.Place and Duration of Study: This study was conducted at the Lahore Medical and Dental College, de’Montmorency College of Dentistry, Fatima Memorial Hospital, University of Lahore and CMH college of Dentistry over a period of months from July to September 2018.Materials and Methods: A questionnaire that was distributed amongst various teaching dental institutes in Lahore after the approval from ethical committees of all these institutions. Data collected was analyzed through SPSS version 20; bivariate correlation was used with Pearson correlation coefficient, level of significance was set to p≤0.01.Results: A total of 316 dental practitioners from five dental institutions in Lahore took part in this study. Our data reflected that 72.15% of the study population was familiar with forensic odontology however merely 6.32% of participants have adequate knowledge of subject. Interestingly 82.61% of the house surgeons, 75.64% of the postgraduates and 76% of the faculty members were interested in formal training regarding this subject.Conclusion: The knowledge and practice of forensic dentistry is inadequate but it can expand if proper awareness and education is delivered. This condition could be improved by making forensic odontology an integral part of BDS academic curriculum.